Mediating Role of Entrepreneurial Self-Efficacy and Prosocial Tendency in the Relation Between College Students’ Post-traumatic Growth and Entrepreneurial Intention in the Post-COVID-19 Era - Wang, Lingjie; Huang, Jianhao (Frontiers in Psychology, 2022)
In this study, we explore the psychological mechanisms underlying the relation between college students’ post-traumatic growth and their entrepreneurial intentions in the post-COVID-19 era. Using the post-traumatic growth, entrepreneurial self-efficacy, prosocial tendency, and entrepreneurial intention scales, we tested 690 valid samples of Chinese undergraduates (including 445 men and 245 women). The results revealed that post-traumatic growth of college students in the post-COVID-19 era will have a significant and positive effect on their entrepreneurial intentions. Additionally, the results indicated that students’ entrepreneurial self-efficacy and prosocial tendencies play a partial mediation role between post-traumatic growth and entrepreneurial intentions in the post-COVID-19 era and that there is a chain mediating effect between students’ entrepreneurial self-efficacy and prosocial tendencies. This study provides valuable insights into the influence of post-traumatic growth on entrepreneurial intentions among college students in the post-COVID-19 era and suggests that colleges and universities can improve students’ entrepreneurial intentions by adopting measures to foster their post-traumatic growth, entrepreneurial self-efficacy, and prosocial tendencies.